PENERAPAN MEDIA LITERASI DARING BERBASIS KEARIFAN LOKAL BLITAR (SI CETAR) UNTUK KEGIATAN LITERASI DI UPT SD NEGERI KALIPUCUNG 02 - Widiastuti, Sripit; Putriani , Ida; Wahdati, Dinda Saroh; Anastasya, Ameilya (JURNAL RISET PENDIDIKAN DAN PENGAJARAN, 2022)
The purpose of this study is to describe the application of Blitar local wisdom-based online literacy media and to explain the responses of Kalipucung 02 Public Elementary School students to Blitar local wisdom-based online literacy media. This research uses qualitative and quantitative approaches. This type of research is descriptive research. The results of this study were (1) the Si Cetar media was applied for two days in accordance with the goals of GLS in SD, namely instilling an interest in and fond of reading and (2) the results of students' responses to Si Cetar media were included in the very satisfactory category.